Public Health in Urban Areas: A Bibliometric Analysis of Strategies to Promote Wellbeing and Sustainable Development - Alifah Wilanda; Rezeki Nur; Emdat Suprayitno; Joko Sangaji; Diah Warastuti (Westscience Press, 2024)
This study employs bibliometric analysis to explore the landscape of research on urban public health and sustainability. Utilizing data extracted from major databases spanning from 1992 to 2024, the research identifies key thematic clusters, examines trends over time, identifies gaps presenting future research opportunities, and investigates author collaboration networks. The findings reveal a distinct shift towards integrating urban design with health outcomes, emphasizing the role of green spaces in enhancing mental and physical well-being. Emerging themes such as the impact of pandemics on urban health and the potential of blue spaces in urban settings are highlighted as under-researched areas that offer significant potential for future studies. Furthermore, the analysis of collaboration networks indicates robust intra-field connections and potential for new interdisciplinary partnerships. This study contributes to a deeper understanding of the evolving dynamics within urban public health research and underscores the importance of multidisciplinary approaches in addressing complex urban challenges.